2021
DOI: 10.48550/arxiv.2101.09272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fusion of Majorana Bound States with Mini-Gate Control in Two-Dimensional Systems

Tong Zhou,
Matthieu C. Dartiailh,
Kasra Sardashti
et al.

Abstract: A hallmark of topological superconductivity is the non-Abelian statistics of Majorana bound states (MBS), its chargeless zero-energy emergent quasiparticles. The resulting fractionalization of a single electron, stored nonlocally as a two spatially separated MBS, provides a powerful platform for implementing fault-tolerant topological quantum computing. However, despite intensive efforts, experimental support for MBS remains indirect and does not probe their non-Abelian statistics. Here we propose how to overc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it has also been shown that the presence of critical current minima may not necessarily be associated to transitions between the trivial and TS states [45] and a further analysis of magnetic and crystalline anisotropies of the TS state [46,47] may be needed to better understand the physical origin of the critical current minima [36]. In spite of the challenges, planar JJs continue to attract attention due to their experimental feasibility, versatility, and enhanced region of system parameters supporting the TS state [41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…Furthermore, it has also been shown that the presence of critical current minima may not necessarily be associated to transitions between the trivial and TS states [45] and a further analysis of magnetic and crystalline anisotropies of the TS state [46,47] may be needed to better understand the physical origin of the critical current minima [36]. In spite of the challenges, planar JJs continue to attract attention due to their experimental feasibility, versatility, and enhanced region of system parameters supporting the TS state [41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…Just like with braiding, the result is topologically protected and insensitive to the details of the measurement. Different methods have been proposed to demonstrate the MBS fusion rules [33,[46][47][48][49][50][51][52][53].…”
mentioning
confidence: 99%